Dynamics of anthocyanin and flavonol profiles in the 'Crimson Seedless' grape berry skin during development and ripening - Brar, H.; Singh, Zora; Swinny, E. (Elsevier, 2008)
'Crimson Seedless' grapes (Vitis vinifera L.) do not develop adequate berry colour in different parts of theworld including Australia and USA leading to serious economic losses to the growers. In the present study, various anthocyanins and flavonols were identified in the skin of the 'Crimson Seedless' grapeberries using LC/PDA/ESI-MS and their changes in the berry skin during development and ripening of 'Crimson Seedless' grape berries were investigated during 2005-2006 and 2006-2007. Eleven anthocyanins and two flavonols were identified in the berry skin using LC/PDA/ESI-MS. Of the anthocyanins identified, four anthocyanins including cyanidin 3-O-(600-O-acetyl)-glucoside, peonidin 3-O-(600-O-acetyl)-glucoside, malvidin 3-O-(600-O-acetyl)-glucoside and malvidin 3-O-(600-O-coumaroyl)-glucoside were not reported earlier. During both the years, the concentration of the 3-O-glucosides of delphinidin, petunidin, peonidin, and malvidin as well as the acetyl and coumaroyl esters of the 3-Oglucosides of cyanidin, peonidin, and malvidin in the berry skin increased during berry development and ripening.During 2006-2007, the concentration of cyanidin 3-O-glucoside in the berry skin increased during the early stages of berry ripening and subsequently declined till harvest while in 2005-2006, the concentration increased during the initial phase of berry ripening and remained relatively stable thereafter till harvest. The concentration of total anthocyanins in the berry skin was higher during 2006-2007 as compared to 2005-2006. During both years, the concentration of quercetin 3-O-glucoside in the berry skin increased during berry development and ripening while the concentration of quercetin 3-Oglucuronide in the berry skin decreased during the same period. To the best of our knowledge, this is the first report on the evolution of different anthocyanins and flavonols in the 'Crimson Seedless' berry skin during berry development and ripening.